SOIL IMPROVEMENT OF SOFT GROUND AROUND PILE FOUNDATION IN EARTHQUAKE-RESISTANT DESIGN - T. Ohsutka; G Aramaki; K. Koga (International Association of Lowland Technology, 2004)
When a pile foundation structure is design in soft ground with Japanese road bridge design spesifications, there are many cases in which the cross section, the amount of steel reinforcement, and the number of piles are decided according to the displacement limiting value. In such soft ground, it is possible to expect that displacement magnitude of the base structure is suppressed by improving the soft ground around the piles. This study clarified that there was a depression effect by improving the peripheral grounf of piles, for both the displacement of the base structure and the bending moment in piles. The calculation was carried out variously, by change of improvement depth and improvement width around the pile. Additionally, the effect of soil improvement for nonliniear response of the bridge pier was also examined. In a series of calculations, a two-dimensional finite element analysis program (FLUSH) often used in earthquake-resistant design was used.